Prognostic factor analysis of vitrectomy for myopic foveoschisis. Issue 12 (2nd July 2015) - Lim, Laurence Shen; Ng, Wei Yan; Wong, Doric; Wong, Edmund; Yeo, Ian; Ang, Chong Lye; Kim, Leo; Vavvas, Demetrios; Lee, Shu Yen
Abstract : Purpose: To describe the anatomical and functional outcomes in a cohort of subjects undergoing vitrectomy for myopic foveoschisis, and to analyse the factors predicting foveal reattachment and visual improvement. Methods: This retrospective case series evaluated case records and optical coherence tomography images 6 months after surgery. Multivariate linear and logistic regressions were performed to assess the factors predicting anatomical and visual improvement. Results: In total, 55 eyes of 54 patients were analysed. The mean spherical equivalent refraction was −11.83±4.94D. Foveal detachment was present in 63.5% of eyes preoperatively and subjects with foveal detachment had 0.70 logMAR units (95% CI 0.02 to 1.39) poorer visual acuity than subjects without (p=0.046). The mean preoperative visual acuity was 0.84±0.59 logMAR units and the mean postoperative visual acuity was 0.64±0.64 logMAR units (mean difference 0.20±0.68 logMAR units (p=0.04)). The proportion of eyes with foveal detachment was significantly lower after surgery (12.5%; p<0.001). However, the proportion of eyes with ellipsoid zone disruption was significantly higher after surgery (59.6% vs 34.0%; p<0.001). In multivariate analyses, the preoperative central foveal thickness significantly predicted postoperative visual improvement by two or more lines (OR 1.004 (95% CI 1.000 to 1.007), per μm increase; p=0.049). The presence of ellipsoid zone disruption preoperatively was associated with 0.96 logMAR (95% CI 0.2 to 1.72) poorer final acuity (p=0.02). Conclusions: Eyes with myopic foveoschisis with preoperative ellipsoid disruption and thinner central foveal thickness tend to have poorer visual outcomes. While current surgical manoeuvres are effective in reattaching the fovea, they may also cause iatrogenic injury to the photoreceptors.